Chicago World's Exposition. Grand March. - Victor Vogel::::::::: (National Music Co.)
At head of title on cover: Dedicated by the publishers to all who believe in the eternal fitness of things. On cover is a lithograph of Uncle Sam in front of globe showing the Americas. Score c1890 by F.S. Chandler & Co.